1995
DOI: 10.1111/j.1467-9914.1995.tb00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and the Role of Employment Services in Bulgarian Industry

Abstract: This article is based on two surveys of Bulgarian manufacturing enterprises completed by the International Labour Organization in 1992 The surveys covering both state and private sector firms in this transition economy undergoing severe structural change collected a wealth of data on labour and employment practices at the micro level The authors examine recruitment and vacancy rates in the industrial sector managerial recruitment preferences on the basis of age gender and educational back ground and the recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2001
2001
2001
2001

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Similarly, differences were found in the benefits paid to employees (Dubin and Aharoni, 1981;Milkovich and Newman, 1990). Yet another study found differences in the recruitment strategies of the two sectors (Sziraczki and Windell, 1995). Although a considerable amount of research has compared various organizational practices in the private and public sectors, no attempt has been made to compare HRM practices in their entirety.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, differences were found in the benefits paid to employees (Dubin and Aharoni, 1981;Milkovich and Newman, 1990). Yet another study found differences in the recruitment strategies of the two sectors (Sziraczki and Windell, 1995). Although a considerable amount of research has compared various organizational practices in the private and public sectors, no attempt has been made to compare HRM practices in their entirety.…”
Section: Introductionmentioning
confidence: 99%
“…Διαφορές επίσης βρέθηκαν στα πρόσθετα επιδόματα και σε άλλα οφέλη που χορηγούνται στους εργαζόμενους των δύο τομέων (Dubin and Aharoni 1991). Οι Sziraczki and Windell (1995) αποκάλυψαν διαφορές στις στρατηγικές στρατολόγησης των εργαζομένων ανάμεσα στους δύο τομείς.…”
Section: διαφοροποίηση ιδιωτικού και δημοσίου τομέα ως προς τη δαπunclassified